Persuasion in everyday life five mind shapers - Jennings, Judy.; Schrank, Jeffrey; Simmons, Dan.; Lombardo, Joseph; Learning Seed Company (Lke Zurich, Ill. : Learning Seed, 2007)
Viewing this program is like holding a mirror up to your mind. Use it to explore five often hidden forces that shape beliefs and judgments. How we frame events influences our judgment and beliefs, and the ability to shape perceptual frames is the power to persuade.
Title from title screen.
Teaching guide for this program is available at www.learningseed.com.
Executive producer, Joseph Lombardo.
DVD format.
With English subtitle.
Keywords: Communication; Persuasion (Psychology).